193k views
2 votes
9. Solve for x,
9x - 25
5x + 7
N​

1 Answer

4 votes

Answer:

x = 8

Explanation:

Simplifying

9x + -25 = 5x + 7

Reorder the terms:

-25 + 9x = 5x + 7

Reorder the terms:

-25 + 9x = 7 + 5x

Solving

-25 + 9x = 7 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.

-25 + 9x + -5x = 7 + 5x + -5x

Combine like terms: 9x + -5x = 4x

-25 + 4x = 7 + 5x + -5x

Combine like terms: 5x + -5x = 0

-25 + 4x = 7 + 0

-25 + 4x = 7

Add '25' to each side of the equation.

-25 + 25 + 4x = 7 + 25

Combine like terms: -25 + 25 = 0

0 + 4x = 7 + 25

4x = 7 + 25

Combine like terms: 7 + 25 = 32

4x = 32

Divide each side by '4'.

x = 8

Simplifying

x = 8

User Zsw
by
5.3k points